Handbook of biofuels production : processes and technologies - Luque, Rafael, ....-; Campelo, Juan, ....-; Clark, James H., ....- (Oxford : Woodhead, 2011)
In response to the global increase in the use of biofuels as substitute transportation fuels, advanced chemical, biochemical and thermochemical biofuels production routes are fast being developed. Research and development in this field is aimed at improving the quality and environmental impact of biofuels production, as well as the overall efficiency and output of biofuels production plants. The range of biofuels has also increased to supplement bioethanol and biodiesel production, with market developments leading to the increased production and utilization of such biofuels as biosyngas, biohydrogen and biobutanol, among others. Handbook of biofuels production provides a comprehensive and systematic reference on the range of biomass conversion processes and technology. Part one reviews the key issues in the biofuels production chain, including feedstocks, sustainability assessment and policy development. Part two reviews chemical and biochemical conversion and in turn Part three reviews thermal and thermo-chemical conversion, with both sections detailing the wide range of processes and technologies applicable to the production of first, second and third generation biofuels. Finally, Part four reviews developments in the integration of biofuels production, including biorefineries and by-product valorization, as well as the utilization of biofuels in diesel engines. With its distinguished international team of contributors, Handbook of Biofuels Production is a standard reference for biofuels production engineers, industrial chemists and biochemists, plant scientists, academics and researchers in this area.